Efficient flexible characterization of quantum processors with nested error models. (13th September 2021) - Nielsen, Erik; Rudinger, Kenneth; Proctor, Timothy; Young, Kevin; Blume-Kohout, Robin
Abstract: We present a simple and powerful technique for finding a good error model for a quantum processor. The technique iteratively tests a nested sequence of models against data obtained from the processor, and keeps track of the best-fit model and its wildcard error (a metric of the amount of unmodeled error) at each step. Each best-fit model, along with a quantification of its unmodeled error, constitutes a characterization of the processor. We explain how quantum processor models can be compared with experimental data and to each other. We demonstrate the technique by using it to characterize a simulated noisy two-qubit processor.